Comparisons of mortality and pre-discharge respiratory morbidities in small for gestational age and appropriate-for gestational age premature infants - An Indian Experience - Suyog Tannirwar; Sandeep Kadam; Anand Pandit; Umesh Vaidya; Tushar Parikh; Soni Ankit (Mashhad University of Medical Sciences, 2016)
Background: There is an assumption that fetus with restricted growth with an inappropriate intrauterine environment lies under stress. Although small-for-gestational-age (SGA) infants have higher mortality, difference in the outcome of SGA and appropriate-for-gestational-age (AGA) infants regarding respiratory morbidity is controversial. It seems that respiratory morbidities in SGA neonates is different from neonates with AGA. In this study, we intend to compare the mortality and  respiratory morbidity rates between the preterm small for gestational age (SGA) and appropriate for age (AGA) neonates of less than 34 weeks of gestation. Methods: This analytical cross-sectional study was conducted on 498 preterm neonates with gestational age of < 34 weeks, admitted to the Neonatal Intensive Care Unit. These neonates were categorized into two groups of SGA (n=210) and AGA (n=286). The data analysis was performed, using Student's t-test and Mann-Whitney U test for parametric variables and Chi-square and Fisher's exact tests for nonparametric data. Results: According to the results of the study, the two groups were significantly different in terms of their birth weight (P